CINTA: Solusi Epistemologis Kerukunan Beragama (Kajian Titik Temu Antara Filsafat Perenial dan Tasawuf) - Cucu Setiawan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Today, the interfaith conflicts still occur frequently. This makes us aware of the importance of involving religion to take part in paying attention to these humanitarian problems and trying to solve them together. Involving religion in this case is clear as a proof that religion can be a way out of every problem, since religion is not enough when it is only as a forum to manifest our longing to God. Religion demands a concrete involvement in all ethical problems of humanity. This present study uses a qualitative method of literature review. This paper aims to deepen the study of the religious recognition of love by using Perennial Philosophy and Sufism to make it becomes the epistemological foundation of religious harmony. The result of this study concludes that love, which is the essence of every religion, is a logical and ethical choice in the effort to include religion in the above problem. Religious recognition of love becomes an epistemological solution to the realization of religious harmony. Love has removed the attributes of formality. Love is no longer looking at position, religion, and even at the human’s role and status. By considering love as the essence, people only consider that I am human, you are human, and we are all human. So, when all realize that they are human beings who live because of love, human’s duty is only to love one another.